Epidemiological characterization of immediate transfusion reactions in a public teaching hospital (Research, Society and Development, 2021)
Objectives: To characterize immediate Transfusion Reactions (RT) and analyze the means for diagnosing these reactions. Methodology: This is a research with a retrospective, exploratory and descriptive longitudinal design, carried out at a Public University Hospital in Aracaju – SE, Brazil. All ethical aspects were respected approved by the Research Ethics Committee of the Federal University of Sergipe, data collection took place between 2019 and 2020. Data on transfusion reactions were extracted from the hospital's notification system and were characterized according to national and international protocols, as to the imputability of a Transfusional Reaction with clinical and laboratory criteria and with the temporal bond. The statistical analysis performed on the data was descriptive and inferential according to the researchers' variables and objectives. Results: The date of the transfusion incident and the notification in the system provided an average time of 3.91 days for professionals to notify the TRs. The transfusion history was not completed in 85% (67) of the notifications. The possibility of RT recurrences in these patients occurred between 1 to 18 days after the initial event and only 27% (n=3) were in different units. Final considerations: Transfusion reactions when notified demonstrate a rich source for more adequate care for patients undergoing transfusion treatment with blood components.